Anomali Sea Surface Temperature (SST) Effect and Rain Fall on Forest and Land Fire in Province Riau - Erianto Indra Putra; Erekso Hadiwijoyo (Jurnal Silvikultur Tropika, 2012)
Land and forest fire  that  happening in Riau often occur during the dry season. The climate is one of the natural factors that can affect the occurrence of forest and land fire. In addition to climate conditions, sea surface temperature can also influence the occurrence of fires. Sea surface warming in the Pacific Ocean will cause extreme weather changes in Indonesia that can trigger a great fire due to precipitation changes that occur. To find out the genesis of the fire, it can be seen from the number of Hotspots that are captured by the MODIS satellite. The objective of this research is to know the relationship between warming sea water, rainfall and the incidence of fires in Riau using MODIS hotspot data, SST anomalies and precipitation. This research shows that correlation level between rainfall and hotspot include low level (R2 =10,89%), however, result of statistic analysis (P = 0,00) show that rainfall affect on fire  ccurrence. Hotspot  increase in February-March and July-August on dry season in Riau. Low correlation and Pvalue = 0,302  show that Sea Surface Temperature (SST) anomaly do not affect forest and land fire in Riau.